Pembelajaran Pendidikan Kewarganegaraan Menggunakan Metode Inquiry untuk Meningkatkan Hasil Belajar Siswa - Hotma Siregar; Suryani Suryani (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This study aims to determine whether the application of inquiry learning method can improve student learning outcomes in class XII MIPA I Madrasah Aliyah Negeri 1 Medan 2019/2020 Academic Year. This research is a classroom action research study consisting of 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. Data collection techniques used were observation and test. The test consists of pretest, posttest Cycle I, and posttest Cycle II and observation includes the activities of teachers and students. The results showed an increase in student learning outcomes. The improvement process can be seen starting from the initial test with the breakdown of 49 students obtained by 15 students (30.61%) who received complete scores, while 34 students received incomplete grades. In the first cycle post-test, it increased to 30 students (61.22%) who received complete marks, while 19 students (38.78%) received incomplete grades. In the Post Cycle II out of 49 students, 47 students (95.91%) received complete marks, while 2 students (4.09%) received incomplete grades. Thus it can be concluded that the application of inquiry learning method can improve student learning outcomes in the subject of Civics Education majoring in Madrasah Aliyah Negeri 1 Medan in 2019/2020 Academic Year.